一种降低综放工作面含矸率的放煤方法 (2024)
本发明公开了一种降低综放工作面含矸率的放煤方法，沿工作面每m个放煤支架分为一组，设立一级支架，并以一级支架为单位对工作面进行分段，每个分段内再细分为二级支架及三级支架，包括如下步骤：步骤一：通过椭球体基本理论#imgabs0#确定每组一级支架数量及放煤间隔支架数量；本发明提供了一种在提高综放工作面顶煤回收率的同时，降低综放工作面原煤含矸率的放煤方法，针对综放工作面在提高顶煤回收率的情况下，工作面顶板矸石进入后溜，增加原煤含矸率，采用了单轮分组间隔的放煤方式，克服了单轮顺序放煤、多轮顺序放煤、单轮间隔放煤和多轮间隔等放煤方式在提高回收率的情况下，顶板矸石混入量增多，原煤含矸率增加，煤矿企业矸石排放量大的弊端。 The invention discloses a coal caving method for reducing the gangue-containing rate of a fully-mechanized caving working face. Every m coal caving supports are divided into a group along the workingface, a first-level support is arranged, the working face is segmented with the first-level support as a unit, and each segment is internally divided into a second-level support and a third-level support; the method comprises the following steps that 1, the number of first-level supports and the number of coal caving interval supports in each set are determined through the ellipsoid basic theory.According to the coal caving method, the top coal recovery rate of the fully-mechanized caving working face is increas